Co-administration of SARS-CoV-2 and influenza vaccines in healthcare workers: Results of two vaccination campaigns in a large teaching hospital in Rome - Domenico Pascucci; Alberto Lontano; Luca Regazzi; Eleonora Marziali; Mario Cesare Nurchis; Matteo Raponi; Giuseppe Vetrugno; Umberto Moscato; Chiara Cadeddu; Patrizia Laurenti (Taylor & Francis Group, 2023)
ABSTRACTThe concurrent administration of COVID-19 and influenza vaccines has arisen as a promising approach to bolster protection against respiratory pathogens and improve vaccination rates. However, there remains a lack of data regarding the prevalence of co-administration across several vaccination campaigns, especially among healthcare workers (HCWs). Therefore, this study aims to shed light on the acceptance of co-administration strategies among HCWs during the two campaigns following the introduction of the anti-SARS-CoV-2 vaccine. A retrospective cohort study was conducted among the HCWs of the Fondazione Policlinico Universitario "A. Gemelli" IRCCS, a research hospital in Rome. Hospital administrative databases were accessed to gather information about vaccination for SARS-CoV-2 and influenza during the 2021/2022 and 2022/2023 vaccination campaigns. The study included 7399 HCWs. The co-administration of anti-SARS-CoV-2 and influenza vaccines presented a significant rise in 2022/2023 compared to the previous vaccination campaign (+38%): this was confirmed for every professional category, with the largest increases among resident doctors (+47%) and physicians (+44%), and also for every age category, but it was particularly evident for the youngest health professionals. The probability of co-administration uptake during the 2022/2023 campaign was significantly higher for males, and for those that received co-administration during the 2021/2022 campaign, while the probability was lower for nurses and administrative staff. This study highlights the co-administration procedure as a valuable and effective tool in annual vaccination campaigns for SARS-CoV-2 and influenza. The procedure's safety and streamlined logistics make it increasingly attractive for implementation, particularly among HCWs.